A reduced LPV polytopic look-ahead steering controller for autonomous vehicles. (December 2022) - Kapsalis, Dimitrios; Sename, Olivier; Milanes, Vicente; Molina, John J.
Abstract: This paper presents a novel design of a Linear Parameter Varying (LPV) controller based-on the polytopic approach, for the path-following system of an automated vehicle. The implementation of the proposed steering system is based-on the reduction of the initial 3D (3 Dimensional) polytope that, due to the conservatism of the specific approach suffers from over-bounding. The proposed algorithm aims at tightening the polytope by reducing the vertices and the volume of the polytope that includes the parameter variations i.e the longitudinal velocity of the car, its inverse and, the look-ahead distance of the steering algorithm. In this paper, a novel real-time implementation of the reduced LPV/Polytopic controller is proposed as a real-time optimization problem according to the current measured values of parameters. The novel control system, has been validated in high-fidelity simulations, and to a real-life experiment at a test-bed platform (Renault Zoe) in a private test track for low and higher speeds showing encouraging performance and sustaining good tracking and comfort at the same time. Highlights: Lane-tracking steering control for Autonomous Vehicles for low and high speeds. Lateral control design and experimental validation on an automated test bed platform. A 3D LPV Polytopic reduction algorithm for handling the conservatism of the method. Real-time implementation based on a least-squares quadratic optimization problem.